Quantitative analysis of Searle’s speech acts in four selected English short stories - Khanfar, Adil Malik; Sharafi, Sasan; Yousef, Noor Yaqub (Research Journal in Advanced Humanities, 2023)
This study investigates the quantitative use of Searle’s speech acts in four selected translated-into-English short stories of Tolstoy. It is believed that short stories represent a kind of reflection of real life in literature. However, culture plays its role in determining the use of the speech acts in this genre. The main question raised in the study is whether the speech acts under study are mostly used in the selected short stories. The analysis in the study is done by the methodology of collecting data, counting and tabulating the results. The findings show that all the five speech acts are not mostly used and that there is a clear degree of variation of use among them.